Analysis of Head and Neck Primary Cutaneous Mucinous Carcinoma: An Indolent Tumor of the Eccrine Sweat Glands. Issue 3 (May 2021) - Behbahani, Sara; Pinto, Jessica O.; Wassef, David; Povolotskiy, Roman; Paskhover, Boris
Abstract : Background/Objectives: Primary cutaneous mucinous carcinoma (PCMC) of the head and neck is a rare pathologic entity that is an adenocarcinoma of the eccrine sweat glands. Though it has low metastatic potential, it does have a significant recurrence rate. Due to its rarity, its clinical features are not well-known. Methods: The authors searched the National Cancer Database (NCDB) for all cases of PCMC with primary sites of the skin of the head and neck confirmed histologically diagnosed from 2004 to 2016. Those with missing survival information were excluded. Kaplan-Meier (KM) and Cox proportional-hazards models were used to analyze the epidemiology and survival outcomes of PCMC. Results: The authors analyzed 289 cases. Females were more commonly affected (58.8%; P  < 0.05) with the most common primary sites being the eyelid (41.9%) and scalp/neck (25.3%). The average age of diagnosis was 63.8 years (± SD 12.5). Almost all patients received surgery as standalone treatment (92.7%) with wide local excision being the common surgery performed (36.3%). Mohs surgery represented 15.2% of surgically treated cases. Mean overall survival (OS) was 11.4 years with 5-year and 10-year OS being 85.0% and 78.0%, respectively. Most cases were localized at diagnosis with only 2% metastatic at presentation. KM analysis indicated that surgical procedure type, age, tumor diameter, Charlson-Deyo Comorbidity Score, facility type, and stage were significant predictors of OS ( P  < 0.05). Cox proportional-hazards analysis did not reveal independent association of the aforementioned factors with OS. Conclusion: Primary cutaneous mucinous carcinoma has an excellent prognosis with 98% of cases being diagnosed in Stage I and Stage II. As most cases present in the eyelid, special attention should be given to surgical treatment to ensure optimal aesthetic outcomes in this sensitive region. This study represents the largest cohort of head and neck PCMC studied to date. Abstract : Supplemental Digital Content is available in the text